Você como pronome de segunda pessoa no Brasil: motivações e percursos histórico, literário e gramatical - Fernandes, Elaine Cássia Pereira (2009)
The use of YOU as a second person pronoun in the Brazilian language, has a singular form in the national territory and it is a fact that makes us think about the historical and social changes that led it to this alternative in the closer and right direction to the interlocutor. Through the teorical issues about History of Linguistic Ideas, this work tried to show the reasons that led the YOU to this national option, contracting, this way, the Portuguese language spoken in Brazil with the Portuguese spoken in Portugal, where the use of THOU and YOU shows accurated tints, being the first one an interlocutor´s informal treatment and the second a seminformal one. For building the ways for the literary history about this pronoun, the medieval origins were retaken by the reverencial treatment from the interlocutor, by the process of changes about personal treatment from Portugal to Brazil, by the acceptation and the semantical wear, besides its insertion in the literary scripts through a fast reviewing about literature works from XVII and XVIII centuries and a deeper study about national ones from XIX and XX centuries, cause it was a period of a national affirmation, lots of novel productions and a growing worry about the truth construction for the speach participation from the characters. The construction of the grammatical way allowed confirming how much Linguistical progress could change the relationship to the pronominal meanings, not to mention certificating the conservative character, as Grammar says, by certifying that a linguistic fact, even not questioned, could postpone its legal use in a gramatical script, even it´s being prescritive or descritive